Constitutional 3p26.3 terminal microdeletion in an adolescent with neuroblastoma. Issue 5 (4th May 2017) - Pezzolo, Annalisa; Sementa, Angela Rita; Lerone, Margherita; Morini, Martina; Ognibene, Marzia; Defferrari, Raffaella; Mazzocco, Katia; Conte, Massimo; Gigliotti, Anna Rita; Garaventa, Alberto; Pistoia, Vito; Varesio, Luigi
ABSTRACT: Background: Neuroblastoma (NB) is a common and often lethal cancer of early childhood that accounts for 10% of pediatric cancer mortality. Incidence peaks in infancy and then rapidly declines, with less than 5% of cases diagnosed in children and adolescents ≥ 10 y. There is increasing evidence that NB has unique biology and an chronic disease course in older children and adolescents, but ultimately dismal survival. Methods: We describe a rare constitutional 3p26.3 terminal microdeletion which occurred in an adolescent with NB, with apparently normal phenotype without neurocognitive defects. We evaluated the association of expression of genes involved in the microdeletion with NB patient outcomes using R2 platform. We screened NB patient's tumor cells for CHL1 protein expression using immunofluorescence. Results: Constitutional and tumor DNA were tested by array-comparative genomic hybridization and single nucleotide-polymorphism-array analyses. Peripheral blood mononuclear cells from the patient showed a 2.54 Mb sub-microscopic constitutional terminal 3p deletion that extended to band p26.3. The microdeletion 3p disrupted the CNTN4 gene and the neighboring CNTN6 and CHL1 genes were hemizygously deleted, each of these genes encode neuronal cell adhesion molecules. Low expression of CNTN6 and CNTN4 genes did not stratify NB patients, whereas low CHL1 expression characterized 417 NB patients having worse overall survival. CHL1 protein expression on tumor cells from the patient was weaker than positive control. Conclusion: This is the first report of a constitutional 3p26.3 deletion in a NB patient. Since larger deletions of 3p, indicative of the presence of one or more tumor suppressor genes in this region, occur frequently in neuroblastoma, our results pave the way to the identification of one putative NB suppressor genes mapping in 3p26.3.